ÁGUA EM ESTADO VIVO: conflito socioambiental e r-existência em torno do rio Dendê, Barcarena, Pará - Marcel Theodoor Hazeu (Universidade Federal do Maranhão, 2020)
The Amazon is a hydroterritory and a biome that holds thousands of people, species of fauna and flora. The Dendê River in Barcarena-Pará is part of this scenario. This river is the scene of conflicts of interest between transnational corporations, the state and riverside communities. From documentary study and participant observation, we analyze these conflicts, situating them in a historical-interpretative panorama, focusing on the role of the state and the r-existence of riverside communities. The state apparatus is presented through the action of the Company of Economic Development, the State Secretariat of Environment and Sustainability and the Public Prosecutor. The voice of the communities serves as a counterpart. It can be concluded that state support is fundamental for the advancement of capital over the Dendê hydroterritory, impoverishing it and transforming the way of life of the riverside communities.